K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 1 2020

Theo đề: \(\sqrt[3]{x^3+5x^2}-1=\sqrt{\frac{5x^2-2}{6}}\)

\(\Rightarrow\sqrt[3]{x^3+5x^2}=1+\sqrt{\frac{5x^2-2}{6}}\)

\(Đkxđ:x^2\ge\frac{2}{5}\)

Đặt: \(\hept{\begin{cases}\sqrt[3]{x^3+5x^2}=u\\\sqrt{\frac{5x^2-2}{6}}=v\ge0\end{cases}}\)

Ta được: \(\hept{\begin{cases}x^3+5x^2=u^3\\5x^2-2=6v^2\Rightarrow x^3+2=\left(v-1\right)^3+2\Leftrightarrow x=v-1\\u=1+v\end{cases}}\)

Từ trên ta giải được nghiệm: \(x=-6+2\sqrt{7}\)

17 tháng 10 2015

\(ĐKXĐ:x\le3\)

\(\Leftrightarrow\frac{5x+2\sqrt{3-x}-x}{4}>\frac{6-4+3\sqrt{3-x}}{6}\Leftrightarrow\frac{6x+3\sqrt{3-x}}{6}-\frac{2+3\sqrt{3-x}}{6}>0\Leftrightarrow3x-1>0\Leftrightarrow x>\frac{1}{3}\)

Vậy \(\frac{1}{3}

16 tháng 12 2017

a)x=6

b)x=6

d)x=0.2

16 tháng 10 2015

Vậy S={x|1/3<x bé hơn hoặc =3}